2014
DOI: 10.1177/1066480714547184
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and Family Counselors’ Perceived Ethical Issues Related to Online Therapy

Abstract: Technology use in the practice of couple and family therapy has many advantages. The use of online and technology-based modes of communication for therapy, however, presents several valid ethical concerns. In a survey of 226 licensed Marriage and Family Counselors, students, and supervisors, participants were asked to identify ethical concerns and drawbacks of online therapy. Five themes related to this topic emerged: (a) confidentiality, (b) impact to the therapeutic relationship, (c) licensing and liability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 30 publications
1
55
0
5
Order By: Relevance
“…These meta-analyses included studies that only focused on individual problems such as depression, eating disorders, anxiety disorders, and smoking cessation and did not focus on couple relationships, but they do provide evidence that treatment over the internet can work on an individual level; therefore, internet channels might also work for a myriad of couple issues. Yet, marriage and family therapists report some ethical concerns and hesitations in providing online therapy, including confidentiality issues, relationship and alliance issues, licensing and liability issues, crisis management issues, and training issues (Hertlein, Blumer, & Mihaloliakos, 2014).…”
Section: Internet Resourcesmentioning
confidence: 99%
“…These meta-analyses included studies that only focused on individual problems such as depression, eating disorders, anxiety disorders, and smoking cessation and did not focus on couple relationships, but they do provide evidence that treatment over the internet can work on an individual level; therefore, internet channels might also work for a myriad of couple issues. Yet, marriage and family therapists report some ethical concerns and hesitations in providing online therapy, including confidentiality issues, relationship and alliance issues, licensing and liability issues, crisis management issues, and training issues (Hertlein, Blumer, & Mihaloliakos, 2014).…”
Section: Internet Resourcesmentioning
confidence: 99%
“…There is a vast amount of research examining the use of technology within individual therapy (Bauer, Okon, Meermann, & Kordy, ; Castan ̃o, Bynum, Andre ́s, Lara, & Westhoff, ; Chapman, Baker, Nassar‐McMillan, & Gerler, ; Curtis, McLellan, & Gabellini, ; Foreman et al., ; Rousmaniere, ), but fewer studies examining the use of technology specifically by MFTs (Baltimore, ; Hertlein, Blumer, & Smith, ). Of the available studies, though, findings have indicated that MFTs are using technology in their clinical practice in a variety of ways (Baltimore, ; Blumer, Hertlein, Smith, & Allen, ; Fisher & Fried, ; Hertlein, Blumer, & Mihaloliakos, ; Nelson, ).…”
Section: Technology Usage In Mftmentioning
confidence: 99%
“…() identified that only 79 out of 13, 274 articles focused on the Internet and technology in some way. Prior research has noted that there are clear ethical concerns surrounding best practices and the use of technology for MFT's, including in the areas of (a) confidentiality, (b) dual relationships, (c) issues for crises situations, and (d) licensing and liability (Blumer et al., ; Fisher & Fried, ; Hertlein et al., ; Nelson, ). While these findings suggest that MFTs are using different technologies in their practice, more research is needed to better understand the ethical and legal considerations related to technology use within MFT practice.…”
Section: Technology Usage In Mftmentioning
confidence: 99%
“…Hertlein, Blumer, and Mihaloliakos () examined practitioner perceptions of ethical issues related to the use of online therapy with couples and families. Survey data from a total of 226 participants revealed five themes reflective of drawbacks to the use of technology‐based treatment.…”
Section: Technological Issues Affecting Therapy With Couples and Famimentioning
confidence: 99%
“…Maybe new forms of relationship will develop which are not generally (but maybe for some patients and situations) better or worse than a traditional therapeutic relationship' (p. 51). Hertlein, Blumer, and Mihaloliakos (2015) examined practitioner perceptions of ethical issues related to the use of online therapy with couples and families. Survey data from a total of 226 participants revealed five themes reflective of drawbacks to the use of technology-based treatment.…”
Section: The Therapeutic Relationship and Boundariesmentioning
confidence: 99%